Manhaj at-Tafsīr al-Madrasī li Oemar Bakry - M. Riyan Hidayat (Al-Fanar: Jurnal Ilmu Al-Qur’an dan Tafsir, 2020)
This research is under the topic "Curriculum of the scholarly interpretation of Omar Bakri." Which was written by Sheikh Omar Bakri and has a method and a system of custom in writing and interpretation of the Qur’an. Besides that, he can say the first book in the science of exegesis, especially for students in Islamic schools and institutes in Indonesia. The reason for calling this book a scholastic interpretation is appropriate for what Sheikh Omar Bakri aimed to write this interpretation, I mean, to be a help for Indonesian students in the word of God and learning the Arabic language. It contains only two volumes and was used by the Dar es Salaam Contour Institute for Modern Islamic Education and its branches as educational materials to this modern era. And the last of the statement, we will find the result and the conclusion that this book indicates the interpretation that stands on the five foundations, which is the language, the attempt to reveal the meanings of the Qur’an in education, the matter in social application, the explanation of the ruling of the Qur’an, the disclosure of the causes of the texts, and the dismissal of suspicions. Then his method for this book is the total curriculum and its color is the interpretation of social literature. In the form of the famous language (Populer) and the form of writing for this book is not scientific, then its scholastic interpretation is to present matters of education in understanding the Qur’anic verse according to the status of the Indonesian people and calls for the development of experimental thought (Empiric): rational and scientific.